SPAACE - South-American program and aerospace agency for cooperation and exploration - Roman Gonzalez, Avid (2017)
The ability to develop aerospace technology can also represent in a certain way the technological capacity, the level of development, and the economic capability of a country. The aerospace development requires enormous technical abilities and a significant financial investment. In this sense, it is often necessary to work cooperatively to develop large space missions. For this reason, in the present work, one proposes the creation of a South American Space Agency - SPAACE (South American Program and Aerospace Agency for Cooperation and Exploration). The idea was born as a conclusion of the panel discussions developed during the Aerospace Bolivian Conference - ABC 2014 and ABC 2016. It is hoped that this proposal can become a reality thanks to the initiative of different researchers involved in the topic.